Development of Exercise Variations Instructional Videos Attack Using Punching Pad Taekwondo Beginner Athletes Year 2021 - Rahma Dewi; Manahan Berutu; Bessy Sitorus Pane; Nurkadri Nurkadri (UNIVERSITAS NEGERI MAKASSAR, 2022)
This study aims to find out how the feasibility of instructional video variations of attack training using punching pads for taekwondo novice athletes in 2020. The study was conducted on product trials at taekwondo clubs. TVRI Medan. Address on JL. Capt. Sihombing Stone. Comp. TVRI, Club Taekwondo Taruna Nusantara Medan which is located at Jl. Karya Jaya. Comp. Jaya Syafira. Medan Johor and at Taekwondo Club Gaperta Medan. A study subject is a whole object where several sources or informants can provide information about the video instructional attack training product using a punching pad in development research. The research method is the Research and Development (R&D) method. The results of the development of video instructional attack training using punching pad taekwondo novice athletes from the sports aspect have been categorized very well with a percentage of 87.5%, thus the development product can be categorized as viable and can be used. The development of video instructional attack training using punching pad taekwondo novice athletes from taekwondo coaches has been categorized very well with a percentage of 96.6%, thus the development product can be categorized as feasible and usable. The development of video instructional attack training using punching pad taekwondo novice athletes from media experts has been categorized very well with a percentage of 92%, Thus the development product can be categorized as viable and usable. Conclusion of the development of video instructional attack training using punching pad is an instructional video variation of attack training using punching pad in taekwondo novice athletes in 2021 has an excellent category and is worth using.